MODEL PENDIDIKAN KARAKTER GENERASI ALFA DI ERA DIGITAL: STUDI DI PONPES ISHLAHUL MA’ARIF MONTONG ARE KEDIRI LOMBOK BARAT (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the character education model for Generation Alpha at Pondok Pesantren Ishlahul Ma’arif Montong Are Kediri, West Lombok, in the digital era. Generation Alpha, raised alongside rapid technological advancements, faces challenges such as declining social ethics, digital dependency, and unfiltered information exposure. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that the pesantren implements a character education model based on exemplary behavior, habituation of noble character, strengthening of classical Islamic texts (kitab kuning), and structured religious activities. This model effectively shapes students to become disciplined, morally upright, and spiritually strong individuals while equipping them with adaptive skills suited to digital-age challenges. The institution successfully integrates traditional Islamic values with modern generational needs in a balanced and holistic manner.